2011
DOI: 10.1002/ejlt.201000474
|View full text |Cite
|
Sign up to set email alerts
|

A four year study to determine the optimal harvesting period for Tunisian Chemlali olives

Abstract: Due to the importance of the stage of maturity on several olive pomological parameters and oil quality indices, and to the interest that Tunisian olive oil production has recently received, the optimal harvesting period for the main Tunisian olive cultivar, Chemlali, was assessed. For the first time, a four-season crops study, carried out in three representative geographical areas, was focused on both olive fruit pomological parameters and oil chemical composition at different stages of maturity. The stage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
36
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 25 publications
10
36
2
1
Order By: Relevance
“…Peroxide value of oil extracted from olive fruits at purple stage was higher than that measured for black fruits (Figures 5 and 6). Peroxide value change with fruit maturity agrees with that reported by Gutiérrez et al [3], Salvador et al [6], Rotondi et al [12], Baccouri et al [7], Baccouri et al [13], Youssef et al [14] and Lazzez et al [10]. Kneading conditions (temperature and time) were also examined in the present study to investigate their influences on peroxide values of produced olive oils.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Peroxide value of oil extracted from olive fruits at purple stage was higher than that measured for black fruits (Figures 5 and 6). Peroxide value change with fruit maturity agrees with that reported by Gutiérrez et al [3], Salvador et al [6], Rotondi et al [12], Baccouri et al [7], Baccouri et al [13], Youssef et al [14] and Lazzez et al [10]. Kneading conditions (temperature and time) were also examined in the present study to investigate their influences on peroxide values of produced olive oils.…”
Section: Resultssupporting
confidence: 88%
“…Oil yield observed in the present study agrees with that reported for Memecik cultivar by Nergiz ve Ergönül [26]. Besides of kneading conditions, maturity of olive fruit has been reported to be effective on oil yield [1][2][3][4][5][6][7][8][9][10][11]. Models produced by response surface methodology were given in Table 3.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…On the other hand Yousfi et al (2012) found that VOO extracted from mechanically harvested fruit of Arbequina retains chemical composition and best quality at 3 o C. Hence, mechanical harvesting hinders the deterioration process and increases the shelf life of olive fruits. The nutritional and organoleptic aspects of VOO are based upon phenolics, therefore, to gain a product of economic worth it is important to understand the origin of enzymatic activities undermining phenols metabolism during fruit storage period (Lazzez et al, 2011). Thus, it is important to understand basic biochemistry and molecular dynamics of olive fruit and oil for making its better commercialization in international markets.…”
Section: ! 80mentioning
confidence: 99%